Wednesday. Season 1 [videorecording (DVD)] - Gough, Alfred, 1967-; Millar, Miles (MGM Television Entertainment, 2024)
"Wednesday is a sleuthing, supernaturally infused mystery charting Wednesday Addams₂s years as a student at Nevermore Academy. Wednesday attempts to master her emerging psychic ability, thwart a monstrous killing spree that has terrorized the local town, and solve the supernatural mystery that embroiled her parents 25 years ago, all while navigating her new and very tangled relationships at Nevermore." --